2017
DOI: 10.1371/journal.pone.0186841
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs expression profile in solid and unicystic ameloblastomas

Abstract: ObjectivesOdontogenic tumors (OT) represent a specific pathological category that includes some lesions with unpredictable biological behavior. Although most of these lesions are benign, some, such as the ameloblastoma, exhibit local aggressiveness and high recurrence rates. The most common types of ameloblastoma are the solid/multicystic (SA) and the unicystic ameloblastoma (UA); the latter considered a much less aggressive entity as compared to the SA. The microRNA system regulates the expression of many hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…ROS are generated in great amount during oxidative stress (i.e. an imbalance between oxidant anti-oxidant agents), a condition in which proteins, carbohydrates, lipids and nucleic acids are affected [82]. The production of ROS is an important defence mechanism against pathogen invasion, with close involvement of bone resorption in the case of endodontic lesions [82][83][84][85][86][87].…”
Section: Other Inflammatory Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS are generated in great amount during oxidative stress (i.e. an imbalance between oxidant anti-oxidant agents), a condition in which proteins, carbohydrates, lipids and nucleic acids are affected [82]. The production of ROS is an important defence mechanism against pathogen invasion, with close involvement of bone resorption in the case of endodontic lesions [82][83][84][85][86][87].…”
Section: Other Inflammatory Markersmentioning
confidence: 99%
“…During the process of endodontic infection, the binding of bacterial motifs to Toll-like receptors (TLRs) on the surface of phagocytes leads to the beginning of phagocytosis, inducement of humoral and cellular responses (mediated by lymphocytes B and T, respectively), ROS synthesis and consequent production of inflammatory mediators with cytocines and metalloproteinases (MMPs) [82,83]. The increased expression of ROS-related markers has been associated with the pathogenesis of periapical periodontitis [82][83][84][85][86] at both local and systemic levels [83,[85][86][87].…”
Section: Other Inflammatory Markersmentioning
confidence: 99%
“…However, there is a lack of research analyzing the functions of altered miRNAs in AB tissues. Only 1 study analyzed miRNA expression profiles in solid and unicystic AB [20].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the expression of BCL-2 is increased in KOT, but the expression of mir-16–1 and mir-15a are reduced [ 21 ]. Profile of micro-RNA expression emerged 40 micro-RNAs with different expression in ameloblastoma compare to control group [ 22 ].…”
Section: Diagnostic Markers In Odontogenic Tumorsmentioning
confidence: 99%